Changing Tides: Mothers' Supportive Emotion Socialization Relates Negatively to Third-Grade Children's Social Adjustment in School - Castro, Vanessa L. (Soc Dev, 2017)
Parents' supportive reactions to children's negative emotions are thought to promote children's social adjustment. Research heretofore has implicitly assumed that such reactions are equally supportive of children's adjustment across ages. Recent findings challenge this assumption, suggesting that during middle childhood, socialization practices previously understood as supportive may in fact impede children's social adjustment. We explored this possibility in a sample of 203 third-grade children and their mothers. Using structural equation modeling, we tested associations between mothers' supportive (i.e., problem- and emotion-focused) reactions to children's negative emotions and children's social skills and problems as reported by mothers and teachers. Mothers' supportive reactions predicted greater social adjustment in children as reported by mothers. Inverse associations, however, were found with teachers' reports of children's social adjustment: mothers' supportive reactions predicted fewer socioemotional skills and more problem behaviors. These contrasting patterns suggest potential unperceived costs associated with mothers' supportiveness of children's negative emotions for third-grade children's social adjustment in school and highlight the importance of considering associations between socialization practices and children's various social contexts. The findings also highlight a need for greater consideration of what supportiveness means across different developmental periods.